ANGKUTAN UDARA LOGISTIK CERAH TAHUN 2022 , STUDI KASUS DI BANDARA SOEKARNO HATTA DAN BANDARA PAPUA TAHUN 2022 - arista atmadjati; joni gusmali (LIAISON JOURNAL OF BEST, 2022)
The existence of Soekarno hatta Tangerang and Papua,s airports International Airport are very vital, especially for air cargo transportation. As one of the busiest airports in Indonesia,Soekarrno Hatta airports has an important role as the main gateway for air cargo traffic in the central and eastern regions of Indonesia,as well as Papua,s airports in eastern Indonesia area., in which distributes domestically and internationally, and regional . This study uses a quantitative approach where the research is entitled Analysis of Air Cargo Demand During a Pandemic Period at Soetta and Papua,s . This study uses data collection techniqueswith primary and secondary data collection. The results obtained are the characteristics of demand for air cargo during the pre-pandemic and during the pandemic at Soetta airport and Papua,s airports , which is divided into 8 cargo classifications, namely Dangerous Goods, General Cargo, Live Animal, Marine Product, Newspaper, Perishable Cargo, Human Remain and Valuable Goods. The freight cargo in indo esia even facing pandemic era for 2 years 2022, 2021 but at the other hand the government policy has supported with declared some encouraging regulation to airlines busnissess. At year 2022 regulation said that cargo not only accepted at belly cargo compatement but general cargo could loading at cabin compartment. Thats why the air cargo increase 20,53 % for national growth . specially air cargo at airport Soekarno Hatta air cargo tramendously increase 81,78 % only in AP II area and Soekarno Hatta comparing year of 2019.Keywords: Air Cargo, Demand, Comparison, Pandemic and year 2022.